Olistoliths of the Gualcamayo Formation (Middle Ordovician) embedded into the Silurian-Lower Devonian Rinconada Formation, Eastern Precordillera, Argentina: paleontological, stratigraphic, and basin-model implications (Latin American Journal of Sedimentology and Basin Analysis, 2024)
This contribution provides new paleontological and stratigraphic data for the Eastern Precordillera (San Juan province, Argentina) Ordovician basin. This is based on the description of a group of olistoliths, interpreted herein as coming from the lower beds of the Ordovician Gualcamayo Formation, found embedded within the matrix of the Silurian-early Devonian Rinconada Formation. These olistoliths are characterized by variable dimensions and uniform lithologies, composed of black shales and marlstones or following hectometric limestone blocks related to the San Juan Formation. The Gualcamayo Formation blocks show a graptolite fauna characterized by Holmograptus spinosus, H. bovis, Cryptograptusschaeferi, Paraglossograptus tentaculatus, Archiclimacograptus spp., Atopograptus sp., Pseudophyllograptus sp., Tetragraptus sp., and Xiphograptus sp.; whereas on the bedding plane surfaces, conodont elements of Histiodella sp., Paroistodus horridus, Periodon macrodentatus, and Protopanderodus sp. are found. In the interbedded black shales-marlstones, the trilobites Annamitella sp., Mendolaspis sp., and Carolinites? sp. are observed. The presence of this graptolite fauna allows recording the middle Darriwilian H. spinosus Zone, representing the third record in South America, and enabling a correlation with other outcrops of Precordillera and North America, Australasia, and China. These middle Darriwilian deposits at the La Rinconada section represent the youngest age ever recorded for the drowning phase of the Ordovician carbonate platform (locally referred to as transfacies). This is coherent with a progressive drowning model from north to south and agrees with the diachronism of the base of the Gualcamayo Formation and equivalent units. In addition, the difference between the underlying units of the Rinconada Formation in different sections, together with contrasting thickness measurements, might indicate evidence of the Alto del Tambolar tectonic activity during the Rinconada Formation  accumulation in Eastern Precordillera. These processes were also previously recognized for the deposition of the Tucunuco Group in the Central Precordillera. This study expands the knowledge regarding the carbonate drowning process of the Precordillera basin that occurred during the Middle Ordovician and the effects of the Guandacol Tectonic Phase in the La Rinconada area, never mentioned until this moment.
Keywords: Precordillera Basin; Graptolites; Middle Ordovician; olistolithic melange; Rinconada Formation